THE CORRELATION BETWEEN STUDENTSâ VOCABULARY MASTERY AND SPEAKING SKILL AT FIFTH SEMESTER OF ENGLISH STUDY PROGRAM IN PASIR PENGARAIAN UNIVERSITY - Anova, Candra; Antoni, Rivi; Kasyulita, Evi (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
The purpose of this research was aimed at finding out the correlation between studentsâ vocabulary mastery and speaking skill as well as also the studentsâ mastering in vocabulary mastery and studentsâ skill in speaking at the fifth semester students of english study program in University of Pasir Pengaraian. After analyzing and calculating the data, it was found that r calculated was 0,559 with level significance 0.05, and the degree of freedom (df= n-2) was 22. It means that r- counted was higher than r-table (0.559 > 0.404). So, there is cirrelation between two variables above. Therefore, the research hypothesis is accepted, that said âThere is correlation between studentsâ vocabulary mastery and speaking skill at the fifth semester of English study program in University of Pasir Pengaraianâ.